Green buildings in tropical countries (low rise buildings) - Lim, Ai Ni. (2012)
This report focus on existing green building designs and technologies studied to implement on buildings in a tropical climate like Singapore to reduce energy consumption. These energy efficient designs consist of passive designs, active systems, and Building Integrated Photovoltaic systems (BIPV). The author presents two case studies, (1) Singapore’s Zero Energy Building (ZEB) at Building Construction Authority Academy (BCAA) and (2) Pusat Tenaga Malaysia’s Zero Energy Office (PTM’s ZEO), to further illustrate in detail of the green building features used to achieve a net zero Building Energy Index (BEI).